Effects of an anesthetic mixture of medetomidine, midazolam, and butorphanol and antagonism by atipamezole in rabbits - Kirihara, Yumiko; Kurosaki, Kaoru; Saito, Yoji; Matsuo, Hiroyuki; Kajitani, Naoyo; Takechi, Mayumi (EXPERIMENTAL ANIMALS, 2019)
Medetomidine (MED), midazolam (MID), and butorphanol (BUT) mixed anesthetic (MMB) has been used in laboratory animals since ketamine (KET) was designated as a narcotic in Japan in 2007. We previously reported that MMB produced anesthetic effects in mice and rats. We also demonstrated the efficacy of atipamezole (ATI), an antagonist of MED produced a quick recovery from anesthesia. Anesthetics have various anesthetic effects among different animal species. However, there is little information regarding its effects in rabbits. In the present study, we examined anesthetic effects of MMB compared to KET and xylazine mixed anesthetic (KX). We examined the antagonistic effects of ATI by intramuscular (IM) or intravenous (IV) injection in rabbits. We used the anesthetic score to measure surgical anesthetic duration and recovery time from anesthesia. During the experiments, we measured heart rate, respiratory rate, O2-saturation, and blood pressure. We found there were no significant differences in anesthetic duration and recovery time between MMB and KX. There were no significant differences in heart rate after administration of MMB or KX. Systolic blood pressure at 10 min after administration of MMB was higher than that of KX. The antagonistic effect of ATI by IV injection worked faster than that by IM injection. Overall, MMB is a useful drug that can induce similar anesthetic effects to KX and has an antagonist of ATI that makes rabbits quickly recover from anesthesia. These results may contribute to the welfare of laboratory animals, especially rabbits.